2013
DOI: 10.12816/0001499
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Health Literacy Situations of Patients With Type 2 Diabetes

Abstract: To analyze factors which effect diabetes health literacy (DHL) situations of patients with type 2 diabetes and their relations with sociodemographic variables. Data were collected in a policlinic of a public hospital between 1 and 30 December 2010 through questionnaires from patients with type 2 diabetes who were older than 18 years and accepted to be interviewed. For each correct answer related to DHL situations, the variable was given 1 point and for others, 0 point was given. Thus, a scoring was made to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
0
0
1
Order By: Relevance
“…Patients with poor economic status may also experience problems accessing resources. In particular, they may encounter obstacles in coping with chronic illness (40). In consistence with the results of these studies, our study also found that highincome patients had higher HL levels.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with poor economic status may also experience problems accessing resources. In particular, they may encounter obstacles in coping with chronic illness (40). In consistence with the results of these studies, our study also found that highincome patients had higher HL levels.…”
Section: Discussionsupporting
confidence: 89%
“…3 In the study conducted by Aslantekin et al, the rate of not doing foot care in diabetic patients was found to be 74.3%. 21 In studies examining the relationship between smoking and diabetes; in the study of Chakkarwar, smoking was found to be an important risk factor in the development of diabetic nephropathy. 9 In the study of of the patients were still smoking and the development of diabetic nephropathy from smoking.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted the questions of diabetes health literacy from Ankara Numune Education and Research Hospital, 2011 (27) by considering the tendency and culture of diabetes patients with type 2 in the local area. Finally, we asked 15 questions regarding health literacy for participants, for example, do you know what physical activity you can do when you have diabetes?…”
Section: Data Collectionmentioning
confidence: 99%